Increasing Healthy Start food and vitamin voucher uptake for low income pregnant women (Early Years Collaborative Leith Pioneer Site). Issue 1 (11th April 2016) - Mackenzie, Graham; Dougall, Angela
Abstract : Poverty has a detrimental impact on health and wellbeing. Healthy Start food and vitamin vouchers provide support for low income families across the UK, but at least 25% of eligible women and children miss out. We set out to increase uptake, with an aim of 90% of eligible women and children (n~540 eligible, varying over time) receiving vouchers in the initial team's catchment area by December 2015. Starting with one midwife and one pregnant woman in March 2014 we used the model for improvement to identify ways to improve documentation, sign up, and referral. Weekly data on process measures and monthly data on voucher receipt were plotted on run charts. Comparing medians for January-June 2014 and March-August 2015 there was a 13.3% rise in voucher receipt in Lothian (increase from 313 to 355 women), versus an 8.4% decline for the rest of Scotland (fall from 1688 to 1546 women). Figures varied by team, influenced by staff, family, and area factors. The initial aim proved unrealistic, as signing up a woman for vouchers increases both the numerator and denominator. Accordingly, the percentage uptake has not increased at a regional level (remains at 75%), though the figure for the initiating team ("team 3" in graphs) has increased from 73.0% (January 2014) to 79.0% (November 2015). We have continued testing, achieving recent increases in the number of women referred for welfare rights advice on benefits, tax credits, employment rights, childcare, and debt, securing on average £4, 500 per client during 2015/16 (£404k for 89 clients by mid September 2015). This improvement project, part of the Early Years Collaborative in Scotland, has had a measureable impact on pregnant women across Lothian. Success has relied on testing, an electronic maternity record, rapid dissemination of findings through direct engagement with clinical teams, and persistence. Our findings have relevance across the UK, particularly at a time of worsening finances for many families.